2010
DOI: 10.1143/jpsj.79.123701
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Magnetoresistance Hysteresis around the ν=2/3 Quantum Hall State in Tilted Magnetic Field

Abstract: We present an anisotropy of the hysteretic transport around the spin transition point at the Landau level filling factor ν = 2/3 in a tilted magnetic field. When the direction of the in-plane component of the magnetic field B is normal to the probe current I, a strong hysteretic transport due to the current-induced nuclear spin polarization occurs. When B is parallel to I, on the other hand, the hysteresis almost disappears. We also demonstrate that the nuclear spin-lattice relaxation rate T −1 1 at the transi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…10,11) In addition, an anisotropy of the hysteretic transport for the angle between current direction and in-plane magnetic field around the transition point in a tilted magnetic field was found. 12) This suggests that the dynamics of electron spin domains is affected by the current direction for the in-plane field. However, details of the domain structure are still unclear, and the real cause of the magnetoresistance enhancement remains a riddle even now.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10,11) In addition, an anisotropy of the hysteretic transport for the angle between current direction and in-plane magnetic field around the transition point in a tilted magnetic field was found. 12) This suggests that the dynamics of electron spin domains is affected by the current direction for the in-plane field. However, details of the domain structure are still unclear, and the real cause of the magnetoresistance enhancement remains a riddle even now.…”
mentioning
confidence: 99%
“…A previous experiment has shown that the resistanceenhanced state (RES) is not stable and decays over roughly several hundred seconds. 12) In this work, the measurement of the resistance is performed much faster than the decay time of RES. In order to avoid the heating effect due to the current, we change the measuring current to a sufficiently small value.…”
mentioning
confidence: 99%